Microsimulation and policy analysis - Francesco Figari; Alari Paulus; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2014)
We provide an overview of microsimulation approaches to assess the effects of policy on the income distribution. We focus mainly on the role of tax-benefit policies and review the concept of microsimulation and how it contributes to the analysis of the income distribution in general and policy evaluation in particular. We consider the main challenges and limitations and discuss directions for future developments.
Keywords: C81; D31; H30; I30; 330; Microsimulation models; Income distribution; Tax-benefit policies